Case Report: Nine-year-old with parathyroid adenoma within the piriform sinus - Zenno, Anna; Ramamoorthy, Bhavishya; Hammoud, Dima A.; Quezado, Martha; Zeiger, Martha A.; Jha, Smita (Frontiers in Endocrinology, 2023)
We present the case of a 9-year-old female who presented with symptomatic hypercalcemia from primary hyperparathyroidism (PHPT). Labs revealed elevated serum calcium 12.1 mg/dL (ref: 9.1-10.4), ionized calcium 6.8 (ref: 4.5-5.6) mg/dL, phosphorus 3.8 (ref: 3.3-5.1) mg/dL, 25-OH vitamin D 20.1 (30-100) ng/mL, and elevated intact PTH 70 (15-65) pg/mL consistent with the diagnosis of PHPT. She had persistent hyperparathyroidism after bilateral neck exploration, left thyroid lobectomy and transcervical thymectomy. Neither inferior gland was identified. No parathyroid tissue was seen on histology. Repeat pre-operative imaging identified a 7 mm X 5 mm adenoma on 4DCT not seen on 99Tc-sestamibi parathyroid scan. Patient then underwent a successful redo parathyroidectomy with removal of a submucosal left parathyroid adenoma at the superior aspect of the thyroid cartilage in the piriform sinus. Her biochemical work-up remains consistent with surgical cure 6-months after surgery. Herein we also review common locations for ectopic parathyroid adenomas.